MEMBANGUNN ORGANISASI ISLAM YANG BERKARAKTER: PERAN KEPEMIMPINAN SPIRITUAL - Khoirinnisa, Khoirinnisa; Nasith, Ali (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Leadership is a key element in determining the direction, strategy, and success of an organization. In the context of Islamic organizations, leadership has a broader meaning because it focuses not only on the achievement of worldly goals, but also on the formation of spiritual and moral values rooted in Islamic teachings. Spiritual leadership is an approach to leadership that integrates the worldly aspect with divine values, where the leader acts as a director, guide, as well as an example for the members of the organization. Through the values of honesty, trust, wisdom, and compassion, spiritual leadership is able to form the character of an Islamic organization that has integrity and is oriented towards blessings. This study aims to describe the concept of spiritual leadership in building Islamic organizations with character based on a literature review of Islamic leadership theory and practice. This study uses a qualitative approach with a literature study method. The results of the study show that spiritual leadership is a leadership model that combines worldly and spiritual dimensions. Spiritual leaders not only manage the organization administratively, but also instill faith, moral, and ethical values in every act of leadership.